Kathy H's Struggle For Getting True Love In Kazuo Ishiguro's Never Let Me Go Novel (2005) : An Individual Psychological Approach. - Skripka, Taufik Wahyu, Drs. Abdillah Nugroho, M. Hum, Nur Hidayat, M.Pd (2014)
This study is about struggle for getting true love. The problem of this study is to reveal how the struggle in major character for getting true love is reflected in Never Let Me Go novel created by Kazuo Ishiguro published in 2005. There are two objectives: the first is to analyze the novel in term of structural elements and the second is to analyze the novel based on individual psychological approach . The object of the study is Never Let Me Go novel by Kazuo Ishiguro. It used an individual psychological approach. This study belongs to qualitative research. In this research, there are two types of data, namely primary and secondary data source. The primary data source is the novel and the secondary data is other material related to the study. Both data are collected through library research and analyzed by descriptive analysis. The result of the study shows the following conclusions. First, based on the structural analysis, it is clear that in the Never Let Me Go novel, Kazuo Ishiguro deliver message that struggle for getting true love because it is important in everyone's life because it is absolutely . Second, based on the individual psychological approach the result shows that the most influential aspect in the struggle for getting true love.